Quality of Life, Mental Health and Coping as Determinants of Suicidal Ideation among Farmers with different economic Background - Mehra, Arvind; Gupta, Tamanna; Kumar, Arun; Behmani, Rakesh Kumar (International Journal of Psychosocial Rehabilitation, 2020)
It is widely acknowledged that agricultural is highly stressful occupation, especially in India. India is an agricultural dominant nation, where small farmers are not in a very sound condition economically. The current study investigates the impact of the quality of Life, mental health, and coping as determinants of suicidal ideation among farmers with different economic backgrounds. This study is based on the primary data that has been collected from the eastern zone (four districts) of Haryana state and 375 respondents (with a minimum education of 10th were selected). They were further divided into three different groups as landless farmers, farmers with 1-9 acres land (125), and farmers with more than 9-acre land (125). General Health questionnaire (GHQ), World Health Organization- Quality of life (WHOQOL), Coping Response Inventory (CRI), and Adult Suicidal Ideation Questionnaire (ASIQ) were used for data collection. In statistical tools, descriptive statistic and regression analysis has been applied. The findings of the study reveal significant group differences on different components of quality of life, mental health and different components of coping on suicidal ideation.